Hafnia paralvei ISOLATED FROM AN EMPHYSEMATOUS PYOMETRA IN A BITCH - Rodríguez-Alarcón, Carlos Arturo; Leyva-Varela, Jorge A; García-Herrera, Ricardo; Montoya-Domínguez, Miguel O; Macías-García, Beatriz; Beristain, Diana M (Slovenian Veterinary Research, 2019)
We report the case of a 9-year-old female Labrador retriever, presented to the Veterinary Teaching Hospital with a history of bloody/purulent and malodourous vulvar discharge, decreased appetite and progressive abdominal enlargement for about 20 days. Clinical examination showed a distended and painful abdomen and tympanic sounds on percussion. The patient also presented systemic inflammatory response syndrome (SIRS) and a leukemoid reaction with leukocyte count of 77.9 x 10 /L due to 62.32 x 10 /L lymphocytes. The abdominal radiography showed distended tubular structures occupying most of the abdomen; dorsal displacement of the colon in the left-right lateral projection was also found. The ultrasonographic study also revealed tubular structures in the mid-abdomen that contained flowing fluid presenting mixed echogenicity and hyperechoic particles in suspension. The exploratory celiotomy showed that the uterine horns were distended and contained a mixture of gas and liquid, hence an ovariohysterectomy was performed. The uterine fluid was collected with aseptic technique into a syringe and submitted to the clinical pathology laboratory for aerobic and anaerobic culture and antibiotic sensitivity. Hafnia alvei (now classified as Hafnia paralvei) was identified as the causative bacterial agent. Pyometra caused by gas-producing bacteria is a rare condition and is known as emphysematous pyometra. There are only six reports in the literature of this condition in bitches. A wide range of vaginal bacteria has been found in dogs with pyometra, but to our knowledge this is the first report of emphysematous pyometra caused by Hafnia paralvei in dogs. Key words: veterinary surgery; uterus; emphysematous pyometra; Hafnia paralvei Hafnia paralvei IZOLIRANA IZ EMFIZEMAZOTNE PIOMETRE PRI PSICI Povzetek: V članku poročamo o primeru 9-letne samice pasme labradorec, ki je bil sprejet v Bolnišnici za veterinarsko medicino z anamnezo gnojnih in smrdljivih izločkov iz vulve, zmanjšanim apetitom in postopnim povečevanjem trebuha, kar je trajalo približno 20 dni pred obiskom veterinarja. Klinični pregled je pokazal napihnjen in boleč trebuh in timpanične zvoke ob pretrkavanju. Pacientka je imela tudi sindrom sistemskega vnetnega odziva (SIRS) in povečano skupno število levkocitov (77.9 x 10 /L) zaradi povišanega števila limfocitov (62.32 x 10 /L). Rentgenska slika trebuha je pokazala razširjene cevaste strukture, ki so zasedale večino trebuha; na stranski projekciji (levo-desno) pa so ugotovili tudi dorzalni premik debelega črevesa. Ultrazvočni pregled je prav tako pokazal cevaste strukture v sredini trebuha, ki so vsebovale tekočino mešane ehogenosti s hiperehoičnimi delci v suspenziji. Preiskovalna celiotomija je pokazala, da so bili rogovi maternice raztegnjeni in so vsebovali mešanico plina in tekočine, zato je bila izvedena ovariohisterektomija. Tekočino iz maternice so z aseptično tehniko zbrali v injekcijsko brizgo in jo predali kliničnemu patološkemu laboratoriju za ugotavljanje prisotnosti aerobnih in anaerobnih bakterij ter bakterijske občutljivosti na antibiotike. Hafnio alvei (sedaj razvrščeno kot Hafnia paralvei) so opredelili kot bakterijskega povzročitelja piometre. Piometra, ki jo povzročajo bakterije, ki proizvajajo plin, je redko stanje in je znana kot emfizematozna piometra. V literaturi je opisanih le šest primerov pri psicah. Pri psicah s piometro so našli širok spekter vaginalnih bakterij, vendar je to prvo poročilo o emfizematozni piometri, ki jo povzroča Hafnia paralvei pri psicah. Ključne besede: veterinary surgery; uterus; emphysematous pyometra; Hafnia paralvei